Rape in wartime - Branche, Raphaëlle; Virgili, Fabrice (Genders and sexualities in history, 2012)
Writing about rape in wartime / Raphaëlle Branche, Isabelle Delpla, John Horne, Pieter Lagrou, Daniel Palmieri, Fabrice Virgili -- Categorizing rape in the military law of modern Russia / Marianna G. Muravyeva -- The unquestioned crime: sexual violence by German soldiers during the "War of Annihilation" in the Soviet Union 1941-45 / Regina Mühlhäuser -- The victimization of the body and the body politic during the Greek Civil War, 1945-1949 / Kathrin Stefatos -- Mass rape and the inscription of gendered and racial domination during the Bangladesh War of 1971 / Nayanika Mookherjee -- Rape, blaming the victim and social control in paramilitary enclaves: an approach to the case of Colombia / Natalia Suarez Bonilla -- After "Teutonic fury", "Belgian fury"? fact and fiction in the revenge of Belgian soldiers in the Rhineland in 1923 / Anne Godfroid -- The practices of war, terror and imagination: Moor troops and rapes during the Spanish Civil War / Maud Joly -- Promising rape: private militias against Maoist guerrillas in the state of Bihar (india) / Alexandre Soucaille -- The weight of imagination: rapes and the legend of women snipers in Chechnya / Amandine Regamey -- Breaking the silence: new approaches to the consequences of rape in some African conflicts, 1994-2008 / Nadine Puechguirbal -- The body that writes: reflections on the process of writing about wartime rape avoidance in the Israeli-Palestinian conflict / Tal Nitsan -- The Nigerian civil war of 1967 and the stigmatization of children born of rape victims in Edo State / Adediran Daniel Ikuomola -- "Special decisions" children born as the result of German rape and handed over to public assistance during the Great War (1914-1918) / Antoine Rivière -- The Russians and Germans: rape during the war and post-Soviet memories / Norman M. Naimark